Stop Drug’s Education by National Narcotics Agency towards Students in Palangka Raya City - Tonich Tonich; Ahmad Saefulloh; Nani Setiawati; Esty Pan Pangestie; Eriawaty Eriawaty (Jurnal Penelitian Pendidikan IPA, 2023)
This piece tries to figure out how the BNN Palangkaraya City program teaches kids not to use drugs. This study was started because there are so many stories in the media about students who have been hurt by drug use. This situation makes me worry about the next generation of students if it isn't taken seriously right away by an official organization like BNN Palangka Raya City and with the help of the community. So that this talk can go in a certain direction, the author focuses the study on how BNN Palangkaraya City's anti-drug education programs for students are put into place. This study is a type of detailed qualitative research that looks at things as they are and tries to figure out what they mean. Observation, direct interviews, and written records are all ways to gather data. Snowball sampling methods are used to show the data, reduce the amount of data, and come to conclusions. Source triangulation is used in the data truth method. The data showed that the best way to teach people not to use drugs was through the BNN Goes to School program, which is a partnership between BNN Kota and junior and senior high schools. Second, the literacy program is a partnership between BNN Kota and the mass media for P4GN socialization on national holidays. It also includes three programs for recruiting volunteers and activists who are trained in how to help protect young people from the dangers of drugs.